Strategies to Increase the Competitiveness of Local Products in The Global Market (Study of MSME Products in Tanggamus Regency) - Roby Rakhmadi; Agus Hadiawan; Prasetya Nugeraha (Iapa Proceedings Conference, 2022)
Small, Micro and Medium Enterprises (MSMEs) must be able to become useful institutions for creating the welfare of rural communities. MSMEs must be a space that can create independent communities that gain prosperity and become institutions that can create a higher quality source of livelihood for rural communities. The growth of MSMEs in Tanggamus Regency is not much different from that of the Lampung province But it decreased from 0.959 in 2017 to 0.842 in 2018. In 2019 the growth of MSMEs in Tanggamus Regency increased significantly above the growth of other provinces. Villages have different and diverse characteristics that will have an impact on the working model of MSMEs. Therefore, it is necessary to have a business model that is able to be implementable in a specific context in accordance with the criteria for the MSME model in a village. Therefore, a study of the business model needs to be carried out using quantitative methods. Based on this, this research was carried out in an explanatory manner to find a MSME business model that is adapted to global market segmentation.